A Critical Review on the Translation Book Merleau-Ponty Praising of Philosophy - Somayyeh Rafighi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
A group of professors and philosophers have written a series of articles on the full range of Merleau-Ponty's philosophy, introducing the views of this French phenomenological philosopher, a philosopher who tried to overcome the dichotomies between consciousness and the world as well as consciousness and the body by emphasizing the bodily subject. They aim to acquaint academic and non-university audiences with his ideas. This work, which was published by Cambridge University Press in 2005 in the form of a collection of articles entitled The Cambridge Companion to Merleau-ponty, was translated by Ms. Hanieh Yaseri and published by Ghognoos Publications in Iran in 2012. In this article, we intended to critically examine the Persian translation of this work. Although the author has chosen a valid book for translation, the existence of many formal and content problems, such as not using uniform terms, non-observance of Persian grammar rules, and many inaccuracies, has made the translation of this work have not worthy of its original text and its content don’t understand properly.